Primary amelanotic melanoma of the mandibular gingiva - Kim, Byeong Jun (Arch Craniofac Surg, 2020)
Oral mucosal melanoma is a very rare type of malignant melanoma, the characteristics of which differ from those of cutaneous melanoma. Primary amelanotic melanoma of the mandibular gingiva, which can invade the mandibular bone, is very rare worldwide. Here, we report a case in which we performed a reconstruction of the mandible and gingiva using the fibula osteocutaneous free flap procedure to treat a patient diagnosed with a primary amelanotic melanoma of the mandibular gingiva. The procedure was successful, and no recurrence was observed 10 months after surgery. Oral mucosal melanoma has a much poorer prognosis and a lower 5-year survival rate than cutaneous melanoma. However, recently, immunomodulatory therapies for mutations in melanocytic lesions have been used effectively to treat the increasing number of patients developing this type of melanoma, thus improving the prognosis of patients with oral mucosal melanoma.